Pengaruh Perilaku Konsumen terhadap Keputusan Memilih Pelayanan Refleksi pada Puan Beauty Salon & Spa Padang - Siti Umaya Nur Anisa; Murni Astuti (Lembaga Yasin AlSys, 2026)
Although studies on consumer behavior in the beauty service industry have been widely conducted, research that specifically discusses the influence of consumer behavior on the decision to choose reflexology services at beauty salons in Padang City remains limited. This study aims to describe consumer behavior, describe consumers’ decisions in choosing reflexology services, and analyze the influence of consumer behavior on consumers’ decisions to choose reflexology services at Puan Beauty Salon & SPA in Padang City. This study employed an associative quantitative approach. The study population consisted of all women who used reflexology services at Puan Beauty Salon & SPA in Padang City, with a sample of 73 respondents selected using the total sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and were then analyzed using descriptive analysis and simple linear regression with the aid of SPSS. The results showed that consumer behavior was in the moderate category at 80.8%, while consumer decision-making was also in the moderate category at 78.1%. The hypothesis test showed a positive and significant influence of consumer behavior on the decision to choose reflexology services, with a calculated t-value of 3.857 greater than the t-table value of 1.994 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.162 indicates that consumer behavior contributed 16.2% to consumer decisions, while the remaining 83.8% was influenced by other factors outside this study. These findings confirm that consumer behavior plays a role in the decision to choose reflexology services and provides practical contributions for salon managers in strengthening marketing strategies and improving service quality.